Nutrient Profiling Models in Low- and Middle-Income Countries Considering Local Nutritional Challenges: A Systematic Review - Marie Tassy; Ries van Dijk; Alison L Eldridge; Tsz Ning Mak; Adam Drewnowski; Edith JM Feskens (Current Developments in Nutrition)
Micronutrient deficiencies, undernutrition, and overweight/obesity are prevalent in low- and middle-income countries (LMICs). Nutrient profiling models (NPMs), initially developed to help reduce the prevalence of diet-related chronic diseases in Western countries, could be one solution to promote nutrient-dense foods in LMICs. This study reviewed government-endorsed NPMs implemented in LMICs and assessed their key components in relation to country-specific nutritional challenges. The peer-reviewed and grey literature were systematically reviewed to identify government-endorsed NPMs implemented in LMICs to promote healthier choices among adults. Their key metrics, including scope, components, units, and validation method, were extracted. The prevalence of undernutrition; overweight/obesity; and iron, vitamin A, and iodine deficiencies were extracted from the Global Health Observatory and the Global Burden of Disease study. NPMs have been implemented in 16 LMICs to encourage healthier choices, mostly through front-of-pack labeling schemes. Warning Label schemes are used to strongly discourage the consumption of energy-dense products in countries where overnutrition affects most of the population, such as Latin American LMICs. A “Keyhole” front-of-pack labeling scheme was implemented only in North Macedonia. It limits sugar, fat, and salt while promoting fibers, fruits, vegetables, nuts, and legumes to prevent overnutrition and diet-related chronic diseases. “Choices” schemes that focus on positive messages have been implemented in Southeast Asia and Zambia where over- and undernutrition coexist. “Choices” criteria encourage the consumption of category-specific vitamins and minerals, in addition to advocating limiting certain nutrients. In LMICs, NPMs focus on discouraging the consumption of sugar, fat, and salt. Additionally, NPMs promote category-specific micronutrients in countries where undernutrition remains prevalent or food components associated with a reduced risk of diet-related chronic diseases, including whole grains and fibers, in countries where overnutrition is the main nutrition-related public health issue.This study was registered at PROSPERO as CRD42023468807.